Red-Eye Blink, Bendy Shuffle, and the Yuck Factor A User Experience of Biometric Airport Systems. - Sasse, M.A (IEEE Security and privacy : building confidence in a networked world)
When people find security systems difficult or unacceptable, it can result in bottlenecks, excessive operation costs, and shortcuts or workarounds that undermine security. Since 2001, airports worldwide have deployed an increasing number of security systems with biometric recognition. Some operate behind the scenes, for airport staff or cabin crew use. Airports have been deploying biometrics for travelers, too. Some systems are voluntary, whereas others are required, and store travelers' biometric characteristics for inspection or record. Biometric systems should have user-friendly, intuitive interfaces that guide users in presenting necessary traits. Thus, we must ask whether current biometric systems in airports are usable.